2024
DOI: 10.1021/acsomega.3c09989
|View full text |Cite
|
Sign up to set email alerts
|

Green Organo-Photooxidative Method for the Degradation of Methylene Blue Dye

Adnan Majeed,
Ahmad H. Ibrahim,
Sawsan S. Al-Rawi
et al.

Abstract: This study used an organophoto-oxidative material to degrade the toxic azo dye, methylene blue (MB), due to its hazardous effects on aquatic life and humans. MB is traditionally degraded using metal-based catalysts, resulting in high costs. Several organic acids were screened for organo-photooxidative applications against various azo dyes, and ascorbic acid (AA), also known as vitamin C, was found to be best for degradation due to its high photooxidative activity. It is an eco-friendly, edible, and efficient p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…The response surface methodology and CCD modeling were used to evaluate the individual effects of three independent parameters: concentration of the dye, dose of photooxidative compounds, and time on degradation efficiency. The maximum photodegradation efficiency was 96% under the following optimal conditions: photooxidative compound dosage = 0.015, contact time = 180 min, and concentration of MO = 900 ppm which is more than from methylene blue degradation by Majeed et al 31 The degraded product obtained from MO was 4-(2-(4-aminophenyl) hydrazineyl) benzenesulfonic acid confirmed by HPLC and GCMS analysis. The DFT study was done to support the results of various techniques such as GCMS and HPLC in the degradation mechanism.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The response surface methodology and CCD modeling were used to evaluate the individual effects of three independent parameters: concentration of the dye, dose of photooxidative compounds, and time on degradation efficiency. The maximum photodegradation efficiency was 96% under the following optimal conditions: photooxidative compound dosage = 0.015, contact time = 180 min, and concentration of MO = 900 ppm which is more than from methylene blue degradation by Majeed et al 31 The degraded product obtained from MO was 4-(2-(4-aminophenyl) hydrazineyl) benzenesulfonic acid confirmed by HPLC and GCMS analysis. The DFT study was done to support the results of various techniques such as GCMS and HPLC in the degradation mechanism.…”
Section: Discussionmentioning
confidence: 73%
“…After the addition of AsA into the MO solution under visible light, photodegradation of MO started and the photodegradation process was evaluated every 60 minutes. The MO color change and absorption value decrease as time passes, due to the presence of chromophore resulting the breakdown of N N, 31 indicating the photodegradation process. After 180 minutes, the peak intensity close to zero indicated that MO fully degraded into its fragments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies, such as Chacon-Argaez [69], Borrego Pérez [70], etc., have found that the photocatalytic activity of composites is indeed significantly improved. Mohammed, W [71] et al found that Schottky promoted electron transfer at Ag-TiO 2 , transferred the absorption to the visible region, reduced the band gap of TiO 2, and inhibited electron-hole recombination, thus enhancing the photocatalytic activity and stability.…”
Section: Doping With a Single Transition Metal Elementsmentioning
confidence: 99%